THE CLASSICAL ECONOMIC THEORY AND ITS ROLE IN INTERPRETING THE CONCEPT OF FINANCIAL DOMINANCE ANALYTICAL STUDY - Assistant Teacher Maather Timol Shebl; Asisten Profesor Dr. Maliha Jabbar Abd (Scholars Digest Publishing, 2024)
The research deals with an important topic in the field of interpreting one of the financial aspects of the economic system according to the classical theory, which has diverse opinions according to its thinkers and pioneers, scholars and specialized researchers. The research summarizes what the classical theory included regarding financial hegemony and how it views financial hegemony according to its concept between developed countries and developing or lesser countries. Growth, and thus the research reached a set of important facts that the researcher reached, including that the financial dominance of the classics was an implicit result determined according to the approach of classical economic philosophy and the constants and theoretical visions it produced during the nineteenth century and the beginning of the twentieth century, which believes that economic activity should be left to individuals to according to what their personal interests dictate. They also do not believe that there is a conflict between private interests and public interests, but rather that economic freedom guarantees harmony between these interests.